Business interests, public interests, and experts in parliamentary committees: their impact on legislative amendments in the German Bundestag. Issue 2 (23rd February 2021) - Cross, James P.; Eising, Rainer; Hermansson, Henrik; Spohr, Florian
Abstract: This study examines the evolving role of parliamentary committees in legislative decision-making and their relationships with external actors when amending bills. Drawing on resource dependence theory and informational perspectives on parliamentary committees, we analyse the impact of information provided by business interest organizations, public interest groups, and experts in the German Bundestag's public hearings in 2004, 2007, and 2011. Using a text-reuse approach to capture legislative amendments, we assess the influence of different information types in explaining such changes. Our results show that the Bundestag often amends government proposals, and that interest groups' positions and experts' evidence must be considered when explaining such amendments. We demonstrate that parliament is more responsive to business pressure than to public interest groups, which are heavily dependent on political allies in governing parties. Finally, we show that expert advice can inform policy-makers and legitimize government bills, but can also disempower public interest groups.